3D printed interposer layer for high density packaging of IoT devices - Mondal S.; Mohd Ghazali M.I.; Wijewardena K.; Kumar D.; Chahal P. (Institute of Electrical and Electronics Engineers Inc., 2024)
Indexed by WOS/ Scopus